Faith after the Anthropocene - Wickman, Matthew; Sherman, Jacob (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Recent decades have brought to light the staggering ubiquity of human activity upon Earth and the startling fragility of our planet and its life systems. This is so momentous that many scientists and scholars now argue that we have left the relative climactic stability of the Holocene and have entered a new geological epoch known as the Anthropocene. This emerging epoch may prompt us not only to reconsider our understanding of Earth systems, but also to reimagine ourselves and what it means to be human. How does the Earth's precarious state reveal our own? How does this vulnerable condition prompt new ways of thinking and being? The essays that are part of this collection consider how the transformative thinking demanded by our vulnerability inspires us to reconceive our place in the cosmos, alongside each other and, potentially, before God. Who are we "after" (the concept of) the Anthropocene? What forms of thought and structures of feeling might attend us in this state? How might we determine our values and to what do we orient our hopes? Faith, a conceptual apparatus for engaging the unseen, helps us weigh the implications of this massive, but in some ways, mysterious, force on the lives we lead; faith helps us visualize what it means to exist in this new and still emergent reality.